JOB TRAINING AS A PILLAR OF WORKFORCE DEVELOPMENT: GOVERNMENT EFFORTS TO ENHANCE LABOR COMPETITIVENESS - Ramdan, Muhammad (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
In the era of globalization and rapid technological advancement, the labor market demands a workforce that possesses not only formal education but also skills that align with industry needs. Therefore, the government plays a role in enhancing workforce skills, one of which is through job training programs. This study discusses job training based on labor regulations in Indonesia and examines the role of job training in improving workforce skills to support the goals of workforce development in the country. The research employs a normative juridical method with a statute approach. The findings reveal that job training is regulated under several laws and regulations, including Law Number 13 of 2003 on Manpower, Government Regulation Number 31 of 2006 on the National Job Training System, and various Ministerial Regulations issued by the Ministry of Manpower. The role of job training programs provided by the government is a form of community empowerment, particularly for those classified as part of the labor force, to help them secure decent employment and reduce unemployment rates, thereby contributing to economic growth in Indonesia. This initiative also supports the achievement of Sustainable Development Goal number 8